GAMBARAN PENGETAHUAN IBU PRIMIGRAVIDA TENTANG CARA PEMBERIAN ASI YANG BENAR DI PUSKESMAS HARAPAN RAYA PEKANBARU - Sumami., Delta Meda Aba, (Jurnal Martenity and Neonatal, 2019)
Primigravida is the first pregnant woman. Breastfeeding is a natural process, but often the mothers is unsuccessful or stops breastfeeding early. Many of the reasons given by the mother, among others, the mother does not produce enough ASI or the baby does not want to suct, this is because the mother is less confident that the adequacy enough for the baby, and lack of information on how to give the correct ASI. The purpose of the research is to know the level of primigravida mother about the correct way of goving ASI. The type of research used is quantitative with descriptive design. Based on the results of the study majority of primigravida mothers are knowledgeable as much as 22 respondents (73%) and knowledge less good as much as 8 respondents (27%). The conclusion from the research result shows that majority of primigravida mother of good knowledge is 22 responden (73%), the researcher assumes that one’s knowledge is influenced by education factor and information.